The Prolonged Half-Life of the p53 Missense Variant R248Q Promotes Accumulation and Heterotetramer Formation with Wildtype p53 to Exert the Dominant-Negative Effect - Klemm, Nancy; Schimmer, Roman R.; Konrad, Nils K.; Thelen, Flavian; Fullin, Jonas; Topçu, Ebru; Koch, Christian; Treacy, Milena; Leventhal, Matthew Joseph; Bühler, Marco M.; Lysenko, Veronika; Theocharides, Alexandre P. A.; et al. (Waverly Press, 2025)
Missense mutants of p53 - such as the frequent hotspot variant R248Q - exert a dominant-negative effect (DNE) on wildtype (WT) p53 in cancer cells with monoallelic TP53 mutations. However, the precise functional and molecular mechanisms of the DNE have remained elusive due to a lack of appropriate model systems. Here, we developed a variety of model systems, including CRISPR-edited human isogenic cell lines and transcriptional reporter cell lines, and targeted protein degradation assays that were combined with functional and molecular analyses to functionally characterize the DNE. Formation of heterotetramers between R248Q and WT p53 impaired proper WT p53 functionality by preventing DNA binding and subsequent target gene transactivation. Furthermore, the markedly increased protein half-life of R248Q led to supraphysiologic levels of R248Q, which was critically required for the DNE. Drug-induced targeted protein degradation of R248Q to lower the R248Q:WT ratio restored the transcriptional activity of WT p53, induced anti-proliferative effects in cancer cells in vitro, and elicited strong therapeutic activity in vivo. Together, this study provides mechanistic insights into the DNE of p53 missense mutants and indicates that the DNE represents a promising therapeutic target.